Art in the prehistoric period (the Capsian civilization): a study of some examples of drawings on the shells of ostrich eggs (Journal of Human Sciences, 2022)
This article proposes a study of the art engraved on ostrich eggshell in the prehistoric periods of North Africa, specifically the period of the Capisian civilization in Tunisia. The study of prehistoric science is important in order to understand civilizations that preceded writing and history, and among the most important areas that help us in understanding prehistoric civilizations is the study of works of art, through which we may reach to reveal some features of the lifestyle and daily life in those eras. From this point, we will try to study a part of prehistoric art, which is the Capsian art, by researching the art of engraving, drawing and ornaments on the shells of ostrich eggs.